Early maturation of neural auditory novelty detection - Typical development with no major effects of dyslexia risk or music intervention - Kujala, Teija; Putkinen, Vesa; Virtala, Paula (Elsevier Ireland Ltd., 2025)
Objective
To determine the early development of novelty detection and the effect of familial dyslexia risk and infant music intervention on this development.
Methods
In the longitudinal DyslexiaBaby study, we investigated the maturation of novelty-P3 and late-discriminative negativity (LDN) event-related potentials to novel sounds at birth (N = 177) and at the ages of 6 (N = 83) and 28 months (N = 131).
Results
Novelty-P3 was elicited at all ages, whereas LDN was elicited at 6 and 28 months. Novelty-P3 amplitude was largest at 6 months, and its latency decreased with age. LDN amplitude decreased and latency increased between 6 to 28 months. Dyslexia risk or intervention had no effects, apart from a longer LDN latency in the high-risk than no-risk group.
Conclusions
Already neonates respond to novel environmental sounds, indicating prerequisites for detecting potentially relevant events at birth. Maturation influences neural novelty detection.
Significance
Novelty detection is crucial for perceiving important events, but its early development has been scarcely studied. We found, with a large sample, that neonates detect novel events, and showed the developmental pattern of its neural signature. The results serve as a reference for studies on typical and atypical novelty-detection development in infancy when behavioral testing is challenging.